2014
DOI: 10.1007/978-3-319-05086-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Recursive Complements and Propositional Attitudes

Abstract: The focus of this chapter is in what role syntactic recursion might play in the representation of propositional attitudes. Syntactic complements under mental and communication verbs are recursive, and so also are the propositional attitudes. There is strong evidence that children take some time to master the first order syntactic complementation typical of verbs of communication. When they do acquire these structures, the evidence suggests that this helps children reason about propositional attitudes such as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
2
33
2
Order By: Relevance
“…Similar to the studies showing that language development contributes to the development of first-order ToM [27,42–47] (but see [48] for evidence of false belief understanding in preverbal infants), a number of studies have shown that language is important in children’s development of second-order ToM.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…Similar to the studies showing that language development contributes to the development of first-order ToM [27,42–47] (but see [48] for evidence of false belief understanding in preverbal infants), a number of studies have shown that language is important in children’s development of second-order ToM.…”
Section: Introductionsupporting
confidence: 53%
“…A possible sequence of reasoning steps from the child’s perspective might be as follows: i) “John knows that the chocolate is in the toy box”, ii) “Mary does not know this”, iii) “Mary knows that John put the chocolate into the drawer before”, iv) “Mary thinks that John will look for the chocolate in the drawer”. In line with de Villiers et al [27], each reasoning step is in the form of a single-embedded sentence at the surface. In addition to de Villiers et al’s study, the serial processing bottleneck hypothesis allows us to propose a possible explanation for their failures on children’s development of processing these rules to answer the second-order false belief question in terms of working memory.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations